Pyloric and antral strictures following corrosive acid ingestion: A report of four cases - Shukla, Ram Mohan (Medknow Publications, 2010)
This study reports four children who developed complete stricture of pylorus and antrum of the stomach following accidental ingestion of corrosive agent (toilet cleaner).